Pengaruh Pertumbuhan Ekonomi dan Pendapatan Zakat terhadap Kemiskinan di Sumatra Utara - Hasanah, Nurul; Batubara, Maryam; Syahbudi, Muhammad (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This research aims to determine and assess the impact of zakat income and economic growth on poverty in North Sumatra from 2016 to 2020. This quantitative study uses data from 2016 to 2020 regarding zakat income, economic growth and poverty. use of statistical analysis to illustrate how income from zakat and economic growth affect poverty in North Sumatra. The research results show that the economic growth variable, zakat income, has a significant influence on poverty in North Sumatra. In the T test results, a significant value of 0.625 > 0.05 was achieved when the effect of economic growth (X1) on poverty (Y) was tested. The findings from this test are t count (0.425) t table (2.03) therefore it can be said that economic expansion has a negative impact on poverty. With a significance level of 0.533 > 0.05, the test result of the relationship between poverty (Y) and the zakat income variable (X2) is t count (0.627) > t table (2.03). In the F table test results it is 3.93 and the estimated F value is 4.383 with a 95% confidence level, significant 5% and df (n-k-1) = (60 – 2-1) = 67. This value explains why fcount > ftable = 4.383 > 3.93, so it can be concluded that economic growth (X1) and zakat income (X2) together simultaneously have no significant effect on poverty (Y). Coefficient of determination analysis was carried out to show the level of influence of the two variables. R2 approaches 1 because the influence of the independent variable on the dependent variable increases.